PENGUATAN PENDIDIKAN ISLAM ANAK USIA DINI MELALUI LOMBA FESTIVAL ANAK SHOLEH: KAJIAN KEGIATAN PENGABDIAN MASYARAKAT DI DESA SAIT BUTTU SARIBU - Nurasnida Siregar, Riska; Nursajidah, Indri; Zahra Auliya, Dinda; Ubbah Harahap, Zahrotul; Zahra Lubis, Hilda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to strengthen Islamic early childhood education through the implementation of the Festival Anak Sholeh as part of a community service program in Sait Buttu Saribu Village. The research employed a qualitative approach with an observation method conducted on Monday, July 7, 2025, supported by a literature review to enrich the data. The population of this study consisted of children in Sait Buttu Saribu Village. The findings reveal that the Festival Anak Sholeh positively contributes to the development of religious, social, and moral values in early childhood. Furthermore, the activity fosters interest in learning religion, builds self-confidence, and strengthens Islamic character within an educational and competitive atmosphere. This study emphasizes the importance of collaboration among the community, educators, and village environment in creating sustainable Islamic early childhood education activities.